2018
DOI: 10.5935/1415-2762.20180060
|View full text |Cite
|
Sign up to set email alerts
|

Teaching-Service’s Integration in the Training of Nurses in the State of São Paulo (Brazil)

Abstract: Objetivo: analisar como vem ocorrendo a integração ensino-serviço na formação do enfermeiro, seus avanços e desafios. Método: estudo qualitativo que analisou, por meio da hermenêutica-dialética, os projetos pedagógicos de seis cursos de Enfermagem do estado de São Paulo e as entrevistas de 21 professores. Resultados e Discussão: observa-se que está ocorrendo diversificação dos cenários e inserção dos estudantes na prática profissional nas séries iniciais. A integração ensino-serviço caminha entre avanços e des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0
11

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 8 publications
1
3
0
11
Order By: Relevance
“…It was also observed that the curricula are organized by disciplines distributed in the basic and vocational cycles, as verified by previous studies [19][20][21] . This characteristic dates back to the Flexnerian proposal of fragmentation of medical education -adopted by all health courses -, which defends the mastery of theory in the basic cycle, for further understanding of practice in the professional cycle.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…It was also observed that the curricula are organized by disciplines distributed in the basic and vocational cycles, as verified by previous studies [19][20][21] . This characteristic dates back to the Flexnerian proposal of fragmentation of medical education -adopted by all health courses -, which defends the mastery of theory in the basic cycle, for further understanding of practice in the professional cycle.…”
Section: Discussionsupporting
confidence: 82%
“…Regarding the practical activities, the courses make their students interact with different health devices and community spaces, in accordance with what the DCENF proposes 7 . This diversification of scenarios beyond the hospital environ-ment suggests the understanding of the extended concept of health, contrary to the historically hegemonic process of formation, which focuses on the care of the disease and the hospital as a privileged site for healing and teaching 21 . It also suggests an approximation between the world of education and that of work, so necessary for the development of skills that allow professionals to intervene in the epidemiological profile, thus contributing to improving the quality of life of the populations 20,25,26 .…”
Section: Discussionmentioning
confidence: 99%
“…Embora com grande potencial para mobilização dos atores envolvidos no cuidado e no ensino superior, foram pouco abrangentes. [4][5][6][7] Para desenvolver um processo de ensino-aprendizagem imerso na realidade do cuidado nos serviços da APS, tem-se investido na integração ensino-serviçocomunidade, uma articulação entre academia e instituições de saúde. Todavia, tal aproximação encontra substanciais desafios a serem superados, principalmente em relação ao compartilhamento de objetivos por esses dois mundos, já que a integração ensino-serviço não se constrói isoladamente, mas envolta em processos políticos, sociais e econômicos.…”
unclassified
“…A vivência de ensinar e aprender a práxis do cuidado na APS está envolta por complexidades e subjetividades que suscitam discussões francas, para que o descompasso entre intenções acadêmicas e de assistência possa ser vencido a partir de novas proposições e direcionamentos. 7,10 O movimento de transformação no ensino tem instigado o desenvolvimento de pesquisas sobre a formação do enfermeiro na e para a APS.…”
unclassified
See 1 more Smart Citation